A Reversible Electron Relay to Exclude Sacrificial Electron Donors in the Photocatalytic Oxygen Atom Transfer Reaction with O2 in Water. (25th September 2019) - Vo, Nhat Tam; Mekmouche, Yasmina; Tron, Thierry; Guillot, Régis; Banse, Frédéric; Halime, Zakaria; Sircoglou, Marie; Leibl, Winfried; Aukauloo, Ally
Abstract: Using light energy and O2 for the direct chemical oxidation of organic substrates is a major challenge. A limitation is the use of sacrificial electron donors to activate O2 by reductive quenching of the photosensitizer, generating undesirable side products. A reversible electron acceptor, methyl viologen, can act as electron shuttle to oxidatively quench the photosensitizer, [Ru(bpy)3 ] 2+, generating the highly oxidized chromophore and the powerful reductant methyl‐viologen radical MV +. . MV +. can then reduce an iron(III) catalyst to the iron(II) form and concomitantly O2 to O2 .− in an aqueous medium to generate an active iron(III)‐(hydro)peroxo species. The oxidized photosensitizer is reset to its ground state by oxidizing an alkene substrate to an alkenyl radical cation. Closing the loop, the reaction of the iron reactive intermediate with the substrate or its radical cation leads to the formation of two oxygenated compounds, the diol and the aldehyde following two different pathways. Abstract : Das notwendige Übel sakrifizieller Elektronendonoren in der Photoaktivierung von O2 kann durch Nutzung eines reversiblen Elektronenakzeptors (Methylviologen) umgangen werden. Er fungiert als Träger von Elektronen des angeregten Photosensibilisators, reduziert dann sowohl O2 als auch Fe III und erzeugt eine reaktive Fe III ‐Peroxo‐Spezies für den Sauerstoffatomtransfer. Die Oxidation eines organischen Substrats schließt den photokatalytischen Zyklus.